The Application of PSAK 24 on Employee Benefits in Banking Institutions Listed in Indonesia Stock Exchange - Maisarah Jumaidi; Yossi Diantimala; Syukriy Abdullah (Journal of Accounting Research, Organization and Economics, 2018)
AbstractObjective – This study aims to examine the implementation and differentiation of PSAK 24 regarding employee benefits (Revision 2010) with PSAK 24 (Revision 2013) in the banking institutions listed on the Indonesia Stock Exchange (IDX). Design/methodology – This study analyses secondary data in the form financial statements obtained from IDX. Purposive sampling method was employed with 31 samples. The hypothesis was tested using paired sample t-test. Results – The results showed that banking institutions listed on the Indonesia Stock Exchange (IDX) applied PSAK 24 on employee benefits but there were some banks that in the same year that applied PSAK 24 with different revisions. The average of banks in the period 2013 to 2014 implements PSAK 24 (Revision 2010) which is the first revised PSAK adopting IFRS in it and in the period 2015 to 2016 implements PSAK 24 (Revision 2013) which is the second revised PSAK adopting IFRS in it. In addition, there are differences in implementation between PSAK 24 (Revision 2010) and PSAK 24 (Revision 2013) by the banks listed on the IDX. Research limitations/implications – This study may be limited in its sampling approach and total number of samples used. The findings of this study imply that the application of required accounting standard in Indonesia is still varying particularly within banking institutions. The regulator and standard setter may take further steps in enforcing the relevant accounting standards to achieve more harmonious level of application.